Эколого-географический анализ прямокрылых Харьковской области - Присный, А.В. (Вестник зоологии, 1976)
67 species of Orthoptera are found in the Kharkov Region, 16 of them being mentioned for the first time for this area. In the orthoptera fauna 7 zoogeographical complexes are distinguished: Holarctic (1 species), Transpalearctic (13), Westernpalearctic (5), European.Siberian (20), European (10), Steppe (16), Mediterranean (10). The peculiarities of the Orthoptera ,distribution by biotopes are considered. Disappearance of certain species from the given territory and a wide distribution of others are observed.